Peran Gender dalam Memoderasi Pengaruh Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Rama Krisna Oleh-Oleh Khas Bali - Dhinata, Dwi Mahatma; Kusuma Dewi, Ni Made Wulandari (E-Jurnal Manajemen, 2014)
This study aims to determine the role of gender in moderating the influence of customer satisfaction on customer loyalty. The study was conducted at the customer's Rama Krishna Oleh-Oleh Khas Bali. Sampling method in this study is a non - probability sampling technique in the form of purposive sampling, which is a technique used in determining the sample with the assessment that has been determined by researchers with the number or size of the sample of 60 respondents. Research data collection was conducted through questionnaire method with moderate regression analysis and residuals as data analysis techniques. The test results showed that all variables in this study is valid and reliable. Research data has qualified normality, and heteroscedasticity. The results of the study showed that customer satisfaction has a positive and significant effect on customer loyalty. The result of the interaction between customer satisfaction and gender shows that gender is negatively and significantly moderate the effect of weakening the customer satisfaction to customer loyalty .
Keywords: customer satisfaction; gender; customer loyalty